Examining the effects of hand anthropometric measurements, grip strength and balance skills on shot performance in elite female basketball players - Gür, S.; Soyal, M. (European Journal of Physical Education and Sport Science, 2021)
This study aims to examine the effects of elite female basketball players` hand anthropometric measurements, hand-grip strength and balance skills on their shooting performance. The age, height, weight, body mass index and hand anthropometric values, hand-grip strength and balance of the athletes were measured, and Aahperd shot tests were applied. Data analysis was performed through SPSS 24 package program. Data analyses included the Shapiro-Wilk Test applied to determine whether there is a normal distribution, and Pearson correlation analysis used to evaluate the correlation status of the parameters with the normal distribution of the data. The average age of the 12 female athletes participating in the study was 21.83 ± 4.407 years, the average height was 171.50 ± 6.95 cm, the average body weight was 68.60 ± 17.96 kg and the mean Body Mass Index was 23.99 ± 4.72. has been determined. It was determined that the average right hand grip strength of 12 female athletes participating in the study was 35.92 ± 6.127 kg and the average left hand grip strength was 32.92 ± 5.807 kg. Among the balance parameters, the balance mean deviation value was determined as 07 ±, 048, the balance average speed value as 42 ± 119, the balance path length value as 12.19 ± 3.473 and the balance area value as 02 ±. The Aahperd shot test mean value was also determined to be 18.67 ± 2.425. The analyses regarding the hand anthropometrics parameter of the 12 athletes indicate that there is no significant correlation between shot performance and hand length, width, palm length, third finger length, hand shape index, finger index and hand surface area. Besides, it is determined that there is no significant correlation between the hand grip strength and balance test results and shooting performance. The data revealed that the dominant hand measurements, test values and shooting performance of the athletes are not significantly correlated.